Typography and rhythm-declamation in the Soviet avant-garde: towards a synthesis of image and sound - Ekaterina A. Lavrenteva; Mikhail A. Bronov (Управление культурой)
The article examines the typography of the Soviet avant-garde of the 1920s as a synthetic form of art that combines visual and sound components in a single rhythmic statement. In the context of industrialization, urbanization and revolutionary transformations, the graphic structure of the text turns into an analogue of a sound score, absorbing the rhythms of machines and propaganda speech. The study is based on the theoretical ideas of El Lissitzky, Kazimir Malevich, Nikolai Kulbin, as well as a modern interpretation of the art of typography and poetic experiments of the Russian avant-garde, which allow us to generally understand this art form as a form of visual declamation. Typography is analyzed through the lense of rhythmic declamation and noise music as expressive practices associated with changing the perception of sound and its visualization. Letters and words in the compositions of Rozanova, Zdanevich, Stepanova, Lisitsky, Klutsis and Rodchenko become not just carriers of meaning, but active rhythmic elements, similar to the graphic rhythm of musical notation. Case studies - from "The Tale of Two Squares" to the covers of books and periodicals, collections of musical works, the ability of typography to set the tempo, intonation and visual equivalent of the spoken text is demonstrated. The analysis extends to theatre and cinema, where text operates as a performative element: in Popova’s scenography and Meyerhold’s productions, and in Vertov’s and Eisenstein’s film editing, typography acquires spatial and kinetic dimensions. Avant-garde text leaves the printed page and enters urban environments—storefronts, posters, banners, and propaganda trains—forming a large-scale visual-soundscape of collective action. The study identifies rhythmic organization as a key aesthetic and ideological category that links artistic forms with the socio-cultural context of the time. Avant-garde typography emerges as the language of a new era—an expressive tool that integrates the principles of industrial rhythm, performative text, and the synthetic nature of revolutionary culture.